Hollow glass microspheres/phenolic syntactic foams with excellent mechanical and thermal insulate performance - Wang, Hui; Yan, Rui; Cheng, Hua; Zou, Mingmin; Wang, Hua; Zheng, Kang (Frontiers in Chemistry, 2023)
Syntactic foams with low density as well as low thermal conduction and proper mechanical performance are vitally important for aerospace, marine and automotive industries. Here, phenolic-based syntactic foams were fabricated by combining the hollow glass microsphere (GMs) with phenolic resin of in situ synthesis. Benefited from the stirring and hot-pressing treatment, microspheres dispersed homogeneously in the resin matrix and it greatly reduced the density of the composites. Stretching and compression tests were performed to investigate the mechanical behavior of the foams. It is found that both the compressive and tensile strength decreased as the filler loadings increasing. While the elasticity modulus was improved. On the other hand, thermal properties tests revealed superior thermal stability and thermal insulate performance of the composites. The final residue content of the synthetic foam with 40wt% filler was improved by 31.5% than that of the neat one at 700 oC. And samples with 20 wt% microspheres reached a minimum thermal conductivity value of approximately 0.129 W(m▪K)-1 which is 46.7% lower than that of neat resin (0.298 W(m▪K)-1). This work provides a feasible strategy to construct syntactic foams with low density and ideal thermal properties.